1974
DOI: 10.1111/j.1748-1716.1974.tb05759.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of TRH through the Placenta and Metabolism in the Fetus of the Guinea‐Pig

Abstract: The permeability of the placenta to thyrotropin‐releasing hormone (TRH) and the fetal metabolism of this hormone were studied by giving iodine‐labelled synthetic TRH to pregnant guinea‐pigs during the first trimester. The radioactivities of various tissue fluids (serum, urine, amniotic fluid and maternal bile) and tissue samples (kidney, liver, small intestine, muscle and cortex) of both mother and fetus were counted. The biological activity of the transferred synthetic TRH was measured in fetal serum by bioas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is not clear whether the development and secretion of these cells in anencephalic infants is autonomous or dependent on an extrahypothalamic source of TRH. The following hypotheses can be put for¬ ward: 1) foetal TSH secretion is partially autonom¬ ous or independent of the foetal hypothalamus, 2) foetal secretion is dependent on maternal TRH since it crosses the placenta readily (Lybeck 8c Virkkunen 1974). Recently, however, Tonooka & Greer (1977) have reported that the control of TSH secretion in the foetal rat is completely inde¬ pendent of maternal hypothalamic TRH, and 3) foetal TSH-secreting cells could be stimulated to grow and function by the TRH present in the amniotic fluid and in the placenta (Gibbons et al 1975).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether the development and secretion of these cells in anencephalic infants is autonomous or dependent on an extrahypothalamic source of TRH. The following hypotheses can be put for¬ ward: 1) foetal TSH secretion is partially autonom¬ ous or independent of the foetal hypothalamus, 2) foetal secretion is dependent on maternal TRH since it crosses the placenta readily (Lybeck 8c Virkkunen 1974). Recently, however, Tonooka & Greer (1977) have reported that the control of TSH secretion in the foetal rat is completely inde¬ pendent of maternal hypothalamic TRH, and 3) foetal TSH-secreting cells could be stimulated to grow and function by the TRH present in the amniotic fluid and in the placenta (Gibbons et al 1975).…”
Section: Discussionmentioning
confidence: 99%
“…This hormone is located in the cytoplasm of the syncytiotrophoblast and is released into the fetal circulation (Bajoria & Babawale, 1998; Bajoria et al, 1997). Additionally, the placenta has aminopeptidases that metabolize TRH and regulate the passage of maternal TRH into the fetal circulation (Bajoria et al, 1997; Lybeck & Virkkunen, 1974). Presence of maternal TRH in the fetal circulation has been measured as early as 12 weeks of gestation (Jacobsen et al, 1977; Winters et al, 1974).…”
Section: Th Metabolism In the Placentamentioning
confidence: 99%
“…23 The possibility that chorionic TRH is secreted into the maternal circulation and has some function during pregnancy also remains to be determined. Its possible transfer to the fetus might be considered, but whether the chorionic TRH, like synthetic TRH, [72][73][74] can pass the placenta, is not known.…”
Section: Evidence For Chorionic Trhmentioning
confidence: 99%